2013
DOI: 10.1177/1063426613476091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Check In/Check Out for Students With Internalizing Behavior Problems

Abstract: Internalizing behaviors are directed inward toward the child and are frequently overlooked in classrooms compared with externalizing behaviors. When internalizing behaviors are identified, cognitive-behavioral interventions (CBIs) are typically the intervention of choice; however, CBIs are time-consuming and require considerable skill and experience for successful implementation. An efficient and time-effective targeted intervention for children with internalizing behavior problems is needed. Check In/Check Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 24 publications
6
45
0
Order By: Relevance
“…These findings are consistent with CICO studies conducted in other settings and with different populations (Ennis et al 2012;Hunter et al 2013;Lewis and Moore 2008). This study expands the generalizability of CICO to a new population of students by targeting at-risk kindergarten students in an urban setting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with CICO studies conducted in other settings and with different populations (Ennis et al 2012;Hunter et al 2013;Lewis and Moore 2008). This study expands the generalizability of CICO to a new population of students by targeting at-risk kindergarten students in an urban setting.…”
Section: Discussionsupporting
confidence: 92%
“…Check-In/Check-out has also been used to reduce internalizing behaviors. Hunter et al (2013) implemented CICO with four elementary school students reporting high levels of internalizing behaviors. Results showed that ratings of prosocial replacement behaviors increased, and students' levels of internalizing behaviors decreased as a result of the intervention.…”
Section: Check-in/check-outmentioning
confidence: 99%
“…In studies of CICO or some variation of CICO (e.g., Fabiano et al, 2010;Hunter, Chenier, & Gresham, 2014;Swoszowski, McDaniel, Jolivette, & Melius, 2014), at a minimum, students were involved in checking in with a mentor at the beginning and end of the day and receiving teacher ratings of behavior on a daily report card. The daily report card generally consisted of behavioral expectations (e.g., Be Respectful, Be Responsible) with students rated by their teachers on a scale (e.g., 0 5 did not meet expectations, 1 5 partially met expectations, 2 5 met expectations).…”
Section: Cico Variationsmentioning
confidence: 99%
“…In eight of these studies, authors indicated that daily behavior goals were individualized based on a student's current performance level. For example, Hunter et al (2014) and Simonsen et al (2011) stated students' daily goals were established by averaging the previous 3 days of students' scores on the daily report card. Lane, Capizzi, Fisher, and Ennis (2012) stated, "the actual goals established [were] based on the student's initial performance levels" (p. 63).…”
Section: Cico Variationsmentioning
confidence: 99%
See 1 more Smart Citation